Characteristics and Seasonal evolution of firns and snow cornices in the High Vosges mountains (Eastern France) - Wahl, Laurent; Planchon, Olivier; David, Pierre-Marie (ERDKUNDE, 2009)
Despite their relatively low elevation (about 1300–1400 m) and because of their cold and humid climate, the High Vosges Mountains in eastern France (at about 48°N 7°E) usually experience a long-lasting snow cover and the persistence of residual snow patches into late spring and summer, sometimes until mid-September. Snow accumulation in winter results in the formation of firns and snow cornices. Climate, topography and land cover of the High Vosges are favourable to snow accumulation on the upper leeward edges of fossil glacial cirques. Firns and snow cornices re-form at the same locations. Therefore, 40 sites (including 23 “firn sites” and 17 “cornices sites”) were identified in glacial cirques, most of them facing E to NE and above 1150 m. The variability and succession of weather observed in winter and spring affect on the snow depth and the formation and duration of firns and snow cornices. While snowy winters are followed by a late melting of snow patches (high frequency of NW and N circulation types), mild and winters with little snow cover are followed by an early melting of small firns and snow cornices (high frequency of alternating south-westerly and westerly circulation types). A high frequency of cyclonic/anticyclonic northerly circulation types in spring reduces the snowmelt and sometimes causes new snowfalls. However, heavy rainfall in spring and high temperature in summer cause a rapid snowmelt and disappearance of firns and snow cornices. Slides of firns and cornice collapses increase slope erosion and a serious risk of avalanches occurs during and after snowy winters. Avalanches occur in glacial cirques because of their steep slopes and the Hohneck Massif is particularly subject. A map of the risk of avalanches in the Hohneck Massif in association with the location of the main firns and snow cornices is provided.